On Certain Reversed Mean Lipschitzian Mappings in Banach Spaces. (3rd October 2021) - Bashir, Shahid; Malik, Muhammad Aslam; Husnine, Syed Muhammad
Abstract: We introduce reversed mean Lipschitzian mappings and find the bound for reversed mean Lipschitz constants of its iterates under certain conditions. Moreover, we prove that if a bounded closed and convex subset C of Banach space has fixed point property for nonexpansive mappings, then C also has fixed point property for certain reversed ( ( α, β ), 1 ) -Lipschitzian mappings such that α ≥ β .